Anesthetic Considerations in Pediatric and Adult Tonsillectomy Procedures - Mustiadji, Aji; Ariadi, Ade (Oshada, 2025)
Tonsillectomy remains one of the most frequently performed procedures in otolaryngology, especially in pediatric patients, where anesthetic management is critical for ensuring intraoperative safety and optimizing postoperative outcomes. The complexity of airway access, high risk of airway-related complications, and diversity of international anesthetic guidelines highlight the need for context-specific, evidence based anesthetic strategies. This narrative literature review synthesizes findings from 45 peer-reviewed articles and clinical practice guidelines published between 2015 and 2024. The review focuses on preoperative assessment, intraoperative airway management, and postoperative complication control in both pediatric and adult tonsillectomy. Sources were selected based on relevance, clinical applicability, and methodological rigor. The findings indicate that the use of oral Ring–Adair–Elwyn (RAE) endotracheal tubes (ETT) and reinforced laryngeal mask airways (LMA) offers optimal airway stability, reduces the risk of kinking, and improves surgical field access. ETTs remain the gold standard for securing the airway, especially in cases involving high bleeding risk. Additionally, adequate premedication protocols and antiemetic prophylaxis significantly reduce postoperative nausea and vomiting (PONV). Management of hemorrhage and laryngospasm remains crucial to reduce morbidity. This study concludes that selecting the appropriate airway device particularly ETTs or LMAs based on patient age, anatomy, and surgical technique is vital. Integrating standardized anesthetic protocols with individualized adjustments contributes to safer, more effective tonsillectomy outcomes across varied clinical settings.